Electronic structure and magnetic properties of rare-earth RM₂ and RM₃ compounds - Baranovskiy, A.E.; Grechnev, G.E.; Panfilov, A.S.; Svechkarev, I.V. (Functional Materials, 2004)
Ab initio calculations of the electronic structure and magnetic properties are carried out for the ferromagnetic Gd0₂ compounds (M = Mg, Al, Fe, Co, Ni, Rh, lr, Pt), and also for the La(ln₁-ₓSnₓ)₃ system. Pressure effects on the band structure and magnetic properties of Gd0₂ have been evaluated and supplemented experimentally by magnetic susceptibility x measurements under pressure in the paramagnetic phase. The peculiarities of χ(x) in La(ln₁-ₓSnₓ)₃ alloys are found to originate from the band degeneracy points near the Fermi level. Experimental χ(x) data are analyzed in the framework of modern band and orbital magnetism theories.